Cellulosomal expansin: functionality and incorporation into the complex. Issue 1 (December 2016) - Artzi, Lior; Morag, Ely; Shamshoum, Melina; Bayer, Edward
Abstract Background Expansins are relatively small proteins that lack enzymatic activity and are found in plants and microorganisms. The function of these proteins is to disrupt the plant cell walls by interfering with the non-covalent interchain bonding of the polysaccharides. Expansins were found to be important for plant growth, but they are also expressed by various bacteria known to have interactions with plants.Clostridium clariflavum is a plant cell wall-degrading bacterium with a highly elaborate cellulosomal system. Among its numerous dockerin-containing genes, two expansin-like proteins, Clocl_1862 and Clocl_1298 (termed hereinCcl EXL1 andCcl EXL2) were identified, andCcl EXL1 was found to be expressed as part of the cellulosome system. This is the first time that an expansin-like protein is identified in a cellulosome complex, which implicates its possible role in biomass deconstruction. Results In the present article, we analyzed the functionality ofCcl EXL1. Its dockerin was characterized and shown to bind selectively to type-I cohesins ofC. clariflavum, with preferential binding to the cohesin of ScaG, and additionally to a type-I cohesin ofC. cellulolyticum . We demonstrated experimentally that the expansin-like protein binds preferentially to microcrystalline cellulose, but it also binds to acid-swollen cellulose, xylan, and wheat straw.Ccl EXL1 exhibited a pronounced loosening effect on filter paper, which resulted in substantial decrease in tensile stress. TheC. clariflavum expansin-like protein thus enhances significantly enzymatic hydrolysis of cellulose, both byC. clariflavum cellulosomes and two major cellulosomal cellulases from this bacterium: GH48 (exoglucanase) and GH9 (endoglucanase). Finally, we demonstratedCcl EXL1-mediated enhancement of microcrystalline cellulose degradation by different cellulosome fractions and the two enzymes. Conclusions The results of this study confirm that theC. clariflavum expansin-like protein is part of the elaborate cellulosome system of this bacterium with capabilities of cellulose creeping. The data suggest that pretreatment of cellulosic materials withCcl EXL1 can bring about substantial improvement of hydrolysis by cellulases.